2013
DOI: 10.1053/j.seminoncol.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Related Myelodysplasia and Acute Myeloid Leukemia

Abstract: Therapy-related leukemia (t-MDS/AML) is a well known complication of conventional chemoradiotherapy used to treat a variety of primary malignancies including Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL), acute lymphoblastic leukemia (ALL), sarcoma, and ovarian and testicular cancer. The median time to development of t-MDS/AML is 3 to 5 years, with the risk decreasing markedly after the first decade. t-MDS/AML is the major cause of non-relapse mortality after autologous hematopoietic cell transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
126
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 96 publications
1
126
0
7
Order By: Relevance
“…13 However, recent evidence from our studies and others has revealed that t-MN driver mutations preexist as CHIP before patients are exposed to chemotherapy/radiation therapy. [4][5][6] The current data provide additional evidence that t-MN-associated CNAs can also preexist as CHIP.…”
Section: Discussionmentioning
confidence: 72%
“…13 However, recent evidence from our studies and others has revealed that t-MN driver mutations preexist as CHIP before patients are exposed to chemotherapy/radiation therapy. [4][5][6] The current data provide additional evidence that t-MN-associated CNAs can also preexist as CHIP.…”
Section: Discussionmentioning
confidence: 72%
“…6,7,[13][14][15][16] Here we present a retrospective long-term followup analysis of 79 unselected consecutive t-MDS/t-AML patients who underwent aHCT after predominantly RIC (73.4%) between 1995 and 2014. With a median follow-up of 7.5 years, this is one of the longest reported follow-up studies for this specific patient clientele, revealing a 10 year OS and DFS rate of 24% (13-36%) and 24% (14-36%), respectively, whereas the NRM rate was 32% (22-46%).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The etiology of therapy-related myeloid neoplasms is thought to be related to the mutagenic effect of cytotoxic therapy, including alkylating agents, ionizing radiation therapy, and topoisomerase inhibitors. 1 Typically, therapy-related myeloid neoplasms carry complex and usually unbalanced karyotypic abnormalities, particularly loss of material on the long arm of chromosomes 5 and 7 and rearrangements of the 11q23 region involving the MLL gene. 3 The prognosis of therapy-related myeloid neoplasms is poor, likely due at least in part to the high proportion of cases with adverse karyotype.…”
mentioning
confidence: 99%